Репродуктивная биология и методы селекции сахарной свеклы в ХХ веке - Малецкая, Е.И. (Фактори експериментальної еволюції організмів, 2014)
Aims. Describe the status of work in the field of reproductive biology and breeding of sugar beet with the beginning of work in the field of breeding in Russia. Results. A brief historical review of major achievements in the field of reproductive biology of sugar beet in connection with problems of selection. Conclusions. Briefly outlined the prospects for work in the field of reproductive biology and breeding.

Key words: agamospermy, haploids, reproductive biology, mixoploidy.